Inhibitory immune checkpoint molecules and exhaustion of T cells in COVID-19 - Barnova, M; Bobcakova, A; Urdova, V; Kosturiak, R; Kapustova, L; Dobrota, D; Jesenak, M (Physiological research, 2021)
COVID-19 (Coronavirus Disease) is an infectious disease caused by the coronavirus SARS-CoV-2 (Severe acute respiratory syndrome Coronavirus 2), which belongs to the genus Betacoronavirus. It was first identified in patients with severe respiratory disease in December 2019 in Wuhan, China. It mainly affects the respiratory system, and in severe cases causes serious lung infection or pneumonia, which can lead to the death of the patient. Clinical studies show that SARS-CoV-2 infection in critical cases causes acute tissue damage due to a pathological immune response. The immune response to a new coronavirus is complex and involves many processes of specific and non-specific immunity. Analysis of available studies has shown various changes, especially in the area of specific cellular immunity, including lymphopenia, decreased T cells (CD3+, CD4+ and CD8+), changes in the T cell compartment associated with symptom progression, deterioration of the condition and development of lung damage. We provide a detailed review of the analyses of immune checkpoint molecules PD-1, TIM-3, LAG-3 CTLA-4, TIGIT, BTLA, CD223, IDO-1 and VISTA on exhausted T cells in patients with asymptomatic to symptomatic stages of COVID-19 infection. Furthermore, this review may help to better understand the pathological T cell immune response and improve the design of therapeutic strategies for patients with SARS-CoV-2 infection.
Keywords: T-lymfocyty; Animals; Immune Checkpoint Proteins; interakce hostitele a patogenu; COVID-19; lidé; Signal Transduction; SARS-CoV-2; Host-Pathogen Interactions; signální transdukce; Phenotype; T-Lymphocytes; fenotyp; Humans; proteiny kontrolních bodů imunitní reakce; zvířata